Numerical Analysis of Torsional Reinforcement of Concrete Beams in Unconventional by ANSYS Software - Thaer Jasim Mohammed; Khalid M. Breesem; Abeer F. Hussein (Salehan Institute of Higher Education, 2023)
In this study, a finite element analysis is conducted to study the behaviour of RC beams with different configurations of transverse reinforcement under torsion. These configurations of stirrups are traditional closed stirrups, circular spiral stirrups, and inclined rectangular spiral stirrups. The numerical torsional load values are compared with the experimental torsional load values from previous research. The numerical analysis determined by the ANSYS software shows a reasonable agreement with the experimental torsional load values. The numerical results demonstrate that the use of continuous rectangular spiral stirrups improved the torsional response compared to using another type of beam stirrup. Thus, numerical results show that continuous spiral stirrups are effective at increasing torsional capacity. It is also noted that the behaviour of these beams with continuous spiral stirrups is better than the behaviour of the beams with traditional stirrups. The beams with helical reinforcement, which are TB2, TB3, and TB4 spiral reinforcements, greatly enhanced the toughness. The equivalent stresses are 13.709, 13.728, 14.72, and 15.894 MPa, while the equivalent elastic strains are 0.00421, 0.00377, 0.00347, and 0.00539 mm/mm for the beams TB2, TB3, and TB4, respectively. The beam TB4 had the highest stress and strain value, so its strength improved its ductility properties. As a result, the stirrups' configurations enabled the detection of beam failure mechanisms by improving torsional behaviour when compared to the beam's traditional stirrups. As a result, this research adds more knowledge to the literature on the most effective spiral stirrups for transverse reinforcement to improve the torsional behaviour of beams. Doi: 10.28991/CEJ-2023-09-01-04 Full Text: PDF